A Risk Prediction Model for Breast Cancer Based on Immune Genes Related to Early Growth Response Proteins Family - Xin Zhou; Fang-yuan Zhang; Yan Liu; Dong-xin Wei (Frontiers in Molecular Biosciences, 2021)
Early growth response proteins (EGRs), a transcriptional regulatory family comprised of EGR1, EGR2, EGR3, and EGR 4, are reportedly involved in a vast array of functions. However, EGRs, as a whole, are rarely studied in breast cancer cases. This research was performed based on public datasets. The results demonstrated that, except EGR4, the other EGRs were differentially expressed genes in breast cancer. Subsequently, this study determined the prognosis significance of the EGR family, higher expression levels of EGRs indicating better overall survival (OS) and disease-free survival (DFS), except EGR4. So we attempted to explore the potential mechanism behind the prognostic value of EGRs. At the DNA level, however, neither DNA methylation status nor genetic alterations of EGRs contributed to the prognosis significance. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis revealed that EGRs were involved in several immune-related functions. Afterward, we assessed the correlation between EGRs and the immune system before establishing a risk prediction model with a 14-gene immune signature associated with EGRs, a prognostic nomogram predicting individuals’ 1-, 3-, and 5-year survival probabilities. The risk score was an independent prognosis predictor in the breast cancer cohorts. This study evidenced EGRs’ significance for tumor immunity, demonstrating that the EGR family may be a potential immunotherapeutic target for breast cancer. The 14-gene immune signature is a promising prognostic biomarker in breast cancer.